A Novel Strutless Double-Row Structure for Deep Excavation: Working Mechanism Study and Analysis - Jinqing Jia; Xuegang Pan (Applied Sciences)
This paper presents a novel strut-free earth retaining wall system for excavation, referred to as the asymmetric double-row pile wall (ARPW) retaining system. This system comprises three key elements: front-row reinforced concrete piles, back-row walls, and connecting crossbeams at the top of the piles. This paper aims to analyze the deformation characteristics and mechanical behavior of the ARPW retaining system, double-row pile wall (DRPW) retaining system, and single-row pile wall (SPW) retaining system using both physical model tests and numerical simulations. The study reveals that, with reasonable row spacing, double-row structures exhibit substantially lower earth pressure and bending moments compared to SPW. Additionally, all double-row structures display reverse bending points. The optimal row spacing for DRPW and ARPW is within the ranges of 2D to 6D and 4D to 8D, respectively. ARPW outperforms DRPW by efficiently utilizing active zone friction force and soil weight force (Gs) to resist overturning moments, thereby resulting in improved anti-overturning capabilities, reduced deformations, lower internal forces, and enhanced stability. The study also presents a case study from the Jinzhonghe Avenue South Side Plot in Tianjin, demonstrating the practical application and effectiveness of the ARPW system in meeting stringent deformation requirements for deep foundation pits. These research findings provide valuable insights for practical engineering applications.